STUDI ANALISIS PERBANDINGAN METODE STARTING DIRECT ON LINE (DOL) DAN VARIABEL SPEED DRIVE (VSD) PADA MOTOR FAN UNTUK COOLING TOWER DI PT. RAPP (RIAU ANDALAN PULP PAPER) - Martogi Ivan Putra Naibaho; I Ketut Wijaya; I Made Mataram (Jurnal SPEKTRUM, 2021)
The large starting current in the starting process has the potential to damage theinduction motor. In minimizing the risk of damage, proper starting methods are needed. TheDirect On Line (DOL) method is a starting method commonly used in induction motors becauseof its economical installation and high work efficiency. The starting method which also has goodwork efficiency is the Variable Speed Drive (VSD). There needs to be a comparative analysisbetween the two methods to find out how the performance of the two methods is.Research results, the ongoing performance of the two starting methods on the fanmotor for cooling towers shows that the performance of the VSD method is superior to that ofthe DOL method. Starting performance on an induction motor can be seen from the efficiencyand economic value of the DOL and VSD methods. This performance is of course taking intoaccount the current, rotation speed and the resulting output power.